Digital games based learning for history - problem solving or problematic? - Katrina Foy (University of Aberdeen, School of Education, 2021)
This study follows the design and development of an educational digital game, Tales of Iona, which was designed to be used to promote understanding of the ancient Scottish island of Iona in upper primary or early secondary schools. The game was designed to combine clear pedagogical principles of teaching History with the best of contemporary digital gaming technology. The intention of the game is to engage players in an immersive virtual environment where their interactions with characters, artefacts and historic events through a series of puzzles will develop their understanding of the historical importance of the island of Iona and spark curiosity to learn more about the past. A Design-based Research (DBR) approach was used in this study and the data was collected on a trial day of the prototype of the game. The data was collected from a small sample of players (aged 10-14 years), using methods of questionnaires, interviews and Video Commentary Capture Model (VCCM) to record gameplay and meta-cognition. Analysis of the findings led to improvements to the game design and gave an insight into the way players learn through digital game playing. Conclusions were drawn to the way the game promoted substantive knowledge of the historical context and stimulated further historical enquiry.